The Role of Melatonin in Ewes Reproduction: A Review - Laith Sofian Younis,; Saad Akram Hatif; Qusay Mohammed Aboud (مجلة الانبار للعلوم البيطرية)
This review was assigned to illustrate the melatonin (MLT) effect on reproduction in sheep (ewes). However, the pathway by which MLT charge the seasonal reproduction are imperfectly understood in sheep, the researchers consents that MLT regulates reproduction under influence of day length (photoperiod) to guarantee that birth happen in appropriate date of the year, it’s called neuro-endocrine process. This mechanism mediates by the pineal hormone (MLT). The major role of MLT in ewes is to translate the photo signals into endocrine pulses (gonadotropin-releasing hormone (GnRH) secretion) at the end of the retino-pineal pathway. In sheep, the MLT receptors distributed in premammillary hypothalamus (PMH), pituitary gland and Suprachiasmatic nucleus (SCN), therefore, many brain loci are participating for MLT pathways to modify the seasonal reproduction. Melatonin stimulates GnRH secretion through effect in different regions and neurons in hypothalamus such as a pre-mammillary nucleus, Arcuate and several factors like kisspeptin, RF-amide related peptide-3 (RFRP-3) and Tyrosine Hydroxylase (TH). In addition, its indirectly control prolactin (PRL) output via an effect on Tuberalin release, which is mediate the mechanism of MLT activity on pituitary PRL secretion and regulate his seasonal cyclicity. The alter in day length is the principle ecological factor that control the breeding in seasonal domestic animals. Several reproductive activities are related to short days and begin during autumn when the day becomes short and a decline in temperature (short-day breeder). While expanding in the duration of light lead to a cessation in reproduction activities during late winter and early spring. In conclusion, according to the major physiological role of MLT, it can be used in different aspects in ewes reproduction industry such as induce oestrus, increment the ovulation rate and In vitro embryo production.